The Efficacy of Psychological Intervention on Body Image in Breast Cancer Patients and Survivors: A Systematic-Review and Meta-Analysis - Sebri, Valeria; Durosini, Ilaria; Triberti, Stefano; Pravettoni, Gabriella (Frontiers in Psychology, 2021)
The experience of breast cancer and related treatments has notable effects on women’s mental health. Among them, the subjective perception of the body or Body Image (BI) is altered. Such alterations deserve to be properly treated because they augment the risk for depression and mood disorders, and impair intimate relationships. A number of studies revealed that focused psychological interventions are effective in reducing BI issues related to breast cancer. However, findings are inconsistent regarding the dimension of such effects. This meta-analysis synthesizes and quantifies the efficacy of psychological interventions for BI in breast cancer patients and survivors. Additionally, since sexual functioning emerged as a relevant aspect in the BI distortions, we explored the efficacy of psychological interventions on sexual functioning related to BI in breast cancer patients and survivors. The literature search for relevant contributions was carried out in March 2020 through the following electronic databases: Scopus, PsycINFO, and ProQUEST. Only articles available in English and that featured psychological interventions for body image in breast cancer patients or survivors with controls were included. 7 articles with 17 dependent effect sizes were selected for this meta-analysis. Variables were grouped into: Body Image (6 studies, 9 dependent effect sizes) and Sexual Functioning related to the Body Image in breast cancer patients and survivors (4 studies, 8 dependent effect sizes). The three-level meta-analysis showed a statistically significant effect for Body Image (g = .50; 95% CI [.08; .93]; p < .05) but no significant results for Sexual Functioning related to Body Image (g = .33; 95% CI [-.20; .85]; p = .19). These results suggest that psychological interventions are effective in reducing body image issues but not in reducing sexual functioning issues related to Body Image in breast cancer patients and survivors. Future review efforts may include grey literature and qualitative studies to better understand body image and sexual functioning issues in breast cancer patients. Also, high quality studies are needed to inform future meta-analyses.